If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = -4(-1m + -2) Reorder the terms: -4 = -4(-2 + -1m) -4 = (-2 * -4 + -1m * -4) -4 = (8 + 4m) Solving -4 = 8 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. -4 + -4m = 8 + 4m + -4m Combine like terms: 4m + -4m = 0 -4 + -4m = 8 + 0 -4 + -4m = 8 Add '4' to each side of the equation. -4 + 4 + -4m = 8 + 4 Combine like terms: -4 + 4 = 0 0 + -4m = 8 + 4 -4m = 8 + 4 Combine like terms: 8 + 4 = 12 -4m = 12 Divide each side by '-4'. m = -3 Simplifying m = -3
| (64a^3*b^-6)^2/3 | | (64a^3b^-6)^2/3 | | x^3-2x-1=0 | | 2(-x+3)+5x= | | -3(4x-6)+8x=-6 | | 28=3-5x | | 6(15.2)+20=y | | 10x^2+[-2]+3x^2+5x+5= | | -3*3-9*3= | | 49=7-7x | | -7(-5x+7)=56 | | -3*3-9(3)= | | 2(-x+3)+5= | | -4x+172=6x+20 | | 2x-5/2=3x/2 | | -3(-8k+1)=45 | | -4(1+2x)=84 | | -9*(-45)+5y=-45 | | 7(2+4x)=238 | | 5c=78 | | 2(6x+5)=94 | | x+8(x+2)=5-x | | 192/-12 | | -9x+5*(-45)=-45 | | 4x-1(x-1)=-(x-1)+3x | | 2(3x-5)+x=12x-41solve | | a/2+a/3+a/4 | | 1/2*1/3 | | 3(6-x)=12 | | 1+z=2 | | 5w+10=5+8w | | -5(4x-8)=200 |